FAKTOR YANG BERPENGARUH TERHADAP RISK DISCLOSURE (Studi Empiris Pada Perusahan Perbankan yang Terdaftar di Bursa Efek Indonesia Tahun 2015-2017) - Ingrid Nathaniela; Achmad Badjuri (Faculty of Economic and Business Universitas STIKUBANK, 2018)
This research was conducted to test the effect of corporate governance to risk disclosure of bank firms. Corporate governance are indentifed as the Board Size, The Propotion Of Independent Director, Managerial Ownership, Internasional Ownership, Level Of Profitability and number of audit committe members. The population used in this study is the Banking Company listed ini Indonesia Stock Exchange (IDX) during 2015-2017. Sampling method used is purposive sampling, with a total sampel 66 companies.The test results showed that the variable The Board Size and Managerial Ownership positive and significant on the Risk Disclosure. The Propotion Of Independent Director positive and no significant on the Risk Disclosure. Internasional Ownership, Level Of Profitability and Number Of Audit Committe Members negative and no significant on the Risk Disclosure. Keywords : corporate governance, level of profitability, risk disclosure